Effect Of Raw And Enzyme-Treated Dandelion Leaves And Fenugreek Seed Supplemented Diet On Gut Microflora Of Broiler Chicken (Applied Biological Research, 2016)
Present study was aimed to assess the effects of diet supplemented with  or without enzyme treated 0.5% dandelion (Taraxacum officinale) leaves  (DL) or/and 1% fenugreek (Trigonella foenum graecum) seeds (FS), fed for 42 days on gut microflora of broiler chicken. Cobb chicks (273) were randomly distributed into 7 groups with 13 chicks in each replicate treatment. Birds in control were fed with only basal diet. The study  revealed that caecal total viable and coliform counts were significantly (p
Keywords: Antibacterial; broiler; dandelion; fenugreek; litter